2008
DOI: 10.1111/j.1472-765x.2008.02379.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of Clostridium perfringens isolated from turkey meat by multiplex PCR

Abstract: Aims:  To determine the presence of toxin genes in 22 Clostridium perfringens isolated from turkey meat samples by molecular typing. Methods and Results:  For this purpose, alpha (cpa), beta (cpb), beta 2 (cpb2), epsilon (etx), iota (iA) and enterotoxin (cpe) toxin genes were analysed by multiplex PCR. All 22 turkey meat Cl. perfringens isolates were found to carry the cpa, gene but in none of the isolates cpb, etx, iap or cpe genes were detected. Results showed that all isolates represented type A and were cp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 21 publications
6
11
0
3
Order By: Relevance
“…C. perfringens types prevalent in poultry meat and meat parts conducted in Turkey were similar to those found in our study (8,11,15). Although there are no published data on detection of C. perfringens in poultry edible offal samples, previous studies in Turkey showed that edible offal of broiler can be contaminated with different foodborne pathogens mainly including Salmonella spp.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…C. perfringens types prevalent in poultry meat and meat parts conducted in Turkey were similar to those found in our study (8,11,15). Although there are no published data on detection of C. perfringens in poultry edible offal samples, previous studies in Turkey showed that edible offal of broiler can be contaminated with different foodborne pathogens mainly including Salmonella spp.…”
Section: Discussionsupporting
confidence: 74%
“…The suspensions were mixed and heated at 95°C for 20 min in a water bath (Memmert WB⁄OB 7-45, WBU 45, Schwabagh, Germany) and centrifuged for 3 min at 12 000 g and cooled on ice. A volume of 10 μl was used as a template in the PCR (11).…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted by Erol et al [32], it was found that 12.2% of the turkey meat samples was contaminated by C. perfringens. Sarıgüzel and Erol [33] isolated and identified C. perfringens in 58 of 100 turkey minced meat samples.…”
Section: Resultsmentioning
confidence: 99%
“…In another study of 887 food samples, 278 were positive for C. perfringens but only 10 were also cpe-positive [27]. The type A strain of C. perfringens was detected in 22 of 180 turkey meat samples and most were cpe-negative [28]. Most surveys of animal feces and retail foods report low occurrence rates of cpe-positive C. perfringens.…”
Section: Discussionmentioning
confidence: 99%